Assessment the Natural Radioactivity of Radionuclides ( 226Ra, 232Th, 40K, and 137Cs) in Wheat Grain - Hussein, Zakariya A.; Salih, Najeba F.; Sedeeq, Shalaw Z. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2021)
This paper investigates the activity concentration of radionuclides (226Ra, 232Th, 40K and 137Cs) in the wheat grain samples using a high-purity germanium detector. Thirty-six wheat grain samples were collected from different locations of Koya City, Iraqi Kurdistan region. Average activity concentrations of 226Ra, 232Th and 40K in wheat grain are found to be 0.407 ± 0.097 Bq.kg-1 for 226Ra, 0.36 ± 0.14 Bq.kg-1 for 232Th and 109.25± 2.214 Bq.kg-1 for 40K, respectively. The measured activity concentrations for the radionuclides are compared with the reported data from other countries. In addition, the fallout radionuclide of 137Cs has no detection of in the wheat grain samples. The radium equivalent activity Raeq, internal and external hazard indices Hin and Hex, and annual gonadal dose equivalent are calculated for the measured samples. The total ingestion dose is 113.19 µSv.y-1, which is below the world average value of 290 µSv.y-1.